Increased homocysteine plasma levels in breast cancer patients of a Mexican population - Varela Almanza, K.M.; Puebla-Pérez, A.M.; Delgado-Saucedo, J.I.; Rodríguez-Arévalo, F.; Zúñiga-González, G.M.; Figuera, L.E.; Morán-Mendoza, A.; Gallegos-Arreola, M.P. (Experimental Oncology, 2018)
Aim: Hyperhomocysteinemia has been associated with different pathologies, including cardiovascular diseases, hypertension, diabetes, and breast cancer (BC). To examine the differences in total homocysteine (tHcy) plasma levels, we compared healthy women to BC patients from a Mexican population. Materials and Methods: The tHcy plasma levels were measured using high-performance liquid chromatography with a fluorescence detector in 89 female controls and 261 BC patients. Results: The observed plasma tHcy levels were significantly higher among the BC patients (11.1019 ± 5.9161 µmol/l) compared to the controls (9.1046 ± 1.3213 µmol/l) (p = 0.002), and these differences were evident when stratified by age (≥ 50 years old), menopause status, overweight and obesity, miscarriages, node metastases, progression, subtype classification (luminal, Her2 and triple negative) and nonresponse to chemotherapy. Conclusions: The tHcy plasma levels could be a good marker for the progression and chemosensitivity of BC in the analyzed sample from a Mexican population. Key Words: plasma levels, homocysteine, HPLC, breast cancer, Mexican population.